The logos reader : rational radicalism and the future of politics - Bronner, Stephen Eric, 1949-; Thompson, Michael J., 1973- (University Press of Kentucky, 2006)
Founded in 2002, Logos: A Journal of Modern Society and Culture was established in response to the increasing erosion of a left political culture and the new possibilities for international political engagement and cooperation produced by the Internet. Many of the best known intellectual representatives of what might be termed a "rational radicalism" soon served as the core group for this new online journal that has reached about four million readers. The Logos Reader brings together the most influential and controversial work to appear in the journal. In its pages, writers of exceptional stat.